The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fpls.2015.01142
|View full text |Cite
|
Sign up to set email alerts
|

Foxtail Millet NF-Y Families: Genome-Wide Survey and Evolution Analyses Identified Two Functional Genes Important in Abiotic Stresses

Abstract: It was reported that Nuclear Factor Y (NF-Y) genes were involved in abiotic stress in plants. Foxtail millet (Setaria italica), an elite stress tolerant crop, provided an impetus for the investigation of the NF-Y families in abiotic responses. In the present study, a total of 39 NF-Y genes were identified in foxtail millet. Synteny analyses suggested that foxtail millet NF-Y genes had experienced rapid expansion and strong purifying selection during the process of plant evolution. De novo transcriptome assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 69 publications
4
49
0
1
Order By: Relevance
“…The leaves from composite seedlings with RNAi hairy roots wilted under salt stress for 12 days, and leaves gradually yellowed in composite seedlings with EV-control hairy roots, whereas leaves remained green in composite seedlings with overexpressed hairy roots (Figure 7d). Relative water content (RWC) in plants determines sensitivity to water stress [31]. It was observed that RWC in leaves of soybean composite plants with RNAi hairy roots was significantly lower, and markedly higher in overexpression lines than in the EV-control lines after eight days of drought treatment (Figure 7e).…”
Section: Gmvoz1g Positively Regulates Drought and Salt Stress Toleranmentioning
confidence: 99%
“…The leaves from composite seedlings with RNAi hairy roots wilted under salt stress for 12 days, and leaves gradually yellowed in composite seedlings with EV-control hairy roots, whereas leaves remained green in composite seedlings with overexpressed hairy roots (Figure 7d). Relative water content (RWC) in plants determines sensitivity to water stress [31]. It was observed that RWC in leaves of soybean composite plants with RNAi hairy roots was significantly lower, and markedly higher in overexpression lines than in the EV-control lines after eight days of drought treatment (Figure 7e).…”
Section: Gmvoz1g Positively Regulates Drought and Salt Stress Toleranmentioning
confidence: 99%
“…Resource absorption and transportation are two important resource acquisition processes for roots, with the former being used by cortex and the latter by stele (Guo et al, 2008). The ratio of cortex to stele thickness determines Ceasar et al, 2014 Argonaute protein 1 encoding gene Regulation of stress responses Liu et al, 2016 Abscisic acid stress ripening gene (ASR) Tolerance to drought and oxidative stresses Feng et al, 2016 Autophagy-related gene (ATG) Tolerance to nitrogen starvation and drought stresses Li et al, 2015 Late embryogenesis abundant protein (LEA) Tolerance to salt, osmotic, and drought stresses Wang et al, 2014 ABA-responsive DRE-binding protein (ARDP) Tolerance to salt and drought stresses Li et al, 2014 WD-40 Associated with dehydration stress-responsive pathway Mishra et al, 2012 Acetyl-CoA carboxylase Resistance to sethoxydim herbicide Dong et al, 2011 Dehydration-responsive element-binding protein 2 (DREB2) Dehydration tolerance Lata et al, 2011a NAC transcription factor Salinity tolerance Puranik et al, 2011b Si69 Aluminum tolerance Zhao et al, 2009 Aldose reductase Associated with salinity stress-responsive pathway Veeranagamallaiah et al, 2009 Glutamine synthetase Pyrroline-5-carboxylate reductase Veeranagamallaiah et al, 2007 12-oxophytodienoic acid reductase (OPR1) Drought tolerance Zhang et al, 2007 Photosystem II D1protein Atrazine resistance Jia et al, 2007 Phospholipid hydroperoxide glutathione peroxidase (PHGPX) Associated with salinity tolerance Sreenivasulu et al, 2004 Nuclear factor-Y (SiNF-YA1, SiNFYB8) genes Drought and salt tolerance Feng et al, 2015 Nitrate transporters (SiNRT), Ammonium transporters (SiAMT) Nitrate and ammonium uptake and transport Nadeem et al, 2018 Phosphate transporters (SiPHP) Phosphate transport Ahmad et al, 2018 the suitability of a plant species for adapting to a certain environment for favorable resource distribution. The increased thickness of foxtail millet roots under low N indicates the anatomical modification of stele, where it can accommodate more conduits like vessels and tracheid for efficient transport of N and metabolites.…”
Section: Responses Of Foxtail Millet To N Limitationmentioning
confidence: 99%
“…In mammals, invertebrates, and fungi, there are one or two genes coding for each subunit. Instead, plants have dramatically expanded the number of NF-Y genes: Typically, there are 8 to 14 gene family members for each subunit, conferring an enormous combinatorial capacity on the trimer; some are expressed in a tissue-restricted manner, and many are relatively ubiquitous (Gusmaroli et al, 2001(Gusmaroli et al, , 2002Stephenson et al, 2007;Siefers et al, 2009;Cao et al, 2011b;Hilioti et al, 2014;Liang et al, 2012Liang et al, , 2014Quach et al, 2015;Rípodas et al, 2015;Zhang et al, 2015;Qu et al, 2015;Feng et al, 2015;Ren et al, 2016;Malviya et al, 2016;Li et al, 2016;Yang et al, 2016;Zhang et al, 2016). Typical features of other plant TFs, such as the presence of duplicate members with similar functions and neofunctionalization of specific genes, were determined by genetic experiments, mostly performed in Arabidopsis thaliana (reviewed in Laloum et al, 2013;Petroni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%